2019
DOI: 10.1039/c9sm01650c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein type, concentration and oil droplet size on the formation of repulsively jammed elastic nanoemulsion gels

Abstract: Sodium caseinate (SC)-stabilized 40% oil-in-water nanoemulsions (NEs) could be transformed into elastic gels below a critical droplet size due to increase in ϕeff by a thicker steric barrier of SC, while whey protein (WPI)-stabilized NEs remained liquid due to thinner steric barrier of WPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…From Figure , no change in G’ for the mineral oil NE gels was observed over 90 days, which indicates that the lipid oxidation‐induced mechanism was the most probable reason behind the loss of gel strength in canola oil NE gels. Figure also shows similar long‐term gel stability data for SC NE gels . The gel strength of SC NE gel was higher than the SDS NE gel.…”
Section: Long‐term Stability Of Nanoemulsion Gelssupporting
confidence: 65%
See 1 more Smart Citation
“…From Figure , no change in G’ for the mineral oil NE gels was observed over 90 days, which indicates that the lipid oxidation‐induced mechanism was the most probable reason behind the loss of gel strength in canola oil NE gels. Figure also shows similar long‐term gel stability data for SC NE gels . The gel strength of SC NE gel was higher than the SDS NE gel.…”
Section: Long‐term Stability Of Nanoemulsion Gelssupporting
confidence: 65%
“…However, it was not until the 8 th pass when the average droplet radius was ≈80 nm; the NE converted into a strong self‐supporting gel. Using DLVO interdroplet pair potential, we calculated the overall repulsion beyond the steric barrier between the nanodroplets . It was assumed that the nanodroplets cannot come closer to each other than the interdroplet separation at an electrostatic repulsion of 1 k B T .…”
Section: Effect Of Droplet Size On Nanoemulsion Gelationmentioning
confidence: 99%
“…However, when the NEs were formed with whey protein isolate (WPI), no gelation was observed with 40% oil and 5% WPI, even if the average droplet size was less than 200 nm. 7 The lack of gelation in WPI-stabilized NEs (WPI NEs) was ascribed to the significantly shorter steric layer (∼2 nm 9 ) owing to the compact globular structure of WPI compared to a much longer steric layer of the flexible casein molecule (∼10 nm 1012 ) leading to a low ϕ eff . The lower ϕ eff was responsible for the lack of droplet random jamming and resulted in flowable liquid-like to weak gel behavior in most of the NEs.…”
Section: Introductionmentioning
confidence: 99%
“…The authors proposed that the higher thickness of the casein steric barrier compared to globular whey proteins led to a significant increase in the interfacial shell layer thickness and ϕ eff for the former such that the caseinate-stabilized nanoemulsions achieved a jammed structure. 9 In our previous study, we have also shown an increase in the gel strength of 3 wt% and 5 wt% Citrem (citric acid ester of mono-and diglycerides)-stabilized 40 wt% O/W nanoemulsions upon removal of excess micelles from the continuous phase due to an increase in the thickness of the repulsive barrier around the nanodroplets. 10 Such improved elastic behaviour of the nanoemulsion could make it an alternative structured material for various low-fat food applications.…”
Section: Introductionmentioning
confidence: 87%
“…For example, Erramreddy and Ghosh 8 showed an increase in the gel strength of 40 wt% canola O/W nanoemulsions stabilized by SDS compared to non-ionic Tween 20 due to an increase in the thickness of the repulsive charge cloud around the nanodroplets, which was absent in the case of Tween 20. In another study, Patel et al 9 showed that sodium caseinate-stabilized O/W nanoemulsions were transformed into viscoelastic gels below a critical droplet size, while whey protein stabilized nanoemulsions remained liquid at the same droplet size. The authors proposed that the higher thickness of the casein steric barrier compared to globular whey proteins led to a significant increase in the interfacial shell layer thickness and ϕ eff for the former such that the caseinate-stabilized nanoemulsions achieved a jammed structure.…”
Section: Introductionmentioning
confidence: 99%